Leak locator (rig to real) - M. F., Ghazali; Muhammad Hanafi, Yusop; Mohd Fadhlan, Mohd Yusof; Muhammad Aminuddin, Pi Remli; Abdul Malik, Awang Hamat (2018)
Real time monitoring leak detection and its location through single point analysis. To make the system robust, fire hydrant utilize as point of analysis for direct access with main pipe line system. The fire hydrant cap was designed to fit the pressure sensor and solenoid valve.